Avaliação da qualidade ambiental de aterros sanitários: estudo de caso do aterro metropolitano leste de Aquiraz. - Gusmão, Fábio Teixeira (2019)
The natural environmental degradation caused by anthropic actions such as the inadequate disposal of urban solid waste has been one of the major problems amongst the biggest cities in Brazil. In most of them, becomes evident the lack of public policies based on the percept of an integrated management of waste disposal. According to the National Law nº 12.305/2010, which has instituted the National Policy for Solid Residues, (PNRS), all Brazilian territory must adopt a waste management centre as part of the solution for the final stage of solid waste disposal, working towards a reduction in environmental impact and human health, created mostly by irregular open dumping areas. Considering that, for a greater effectiveness of this purpose, we should seek instruments that contribute to the proper management of the landfill sites, this research sought to asses the environmental quality of the Aterro Sanitário Metropolitano Leste de Aquiraz, using the Landfill Environmental Quality Index (IQAS). The IQAS was prepared based on analyzes and modifications of other indexes, like IQR and IQA to serve as an important tool in order to plan, implement and manage landfills. This present study-case proposed to apply the IQAS as well as providing this tool for the application in other landfills in the State of Ceará and Brazil. The IQAS is composed by 53 indicator wich adress the charactaristics of project, the implanted infrastructure, the local conditions, the operational conditions and the environmental protection systems. To prove the inadequacy of the landfill were analyzed the behaviors of the indicators and the groups of indicators, which were submited by the evaluation criteria established by the proposed index in this study.